Evaluation of neonatal cerebral perfusion using three‐dimensional power Doppler ultrasound volumes. (2nd December 2021) - Kuhasri, Abidev; Jayatilake, Sonali; Stevenson, Gordon; Beirne, Gerrie; Welsh, Alec; Schindler, Timothy
Abstract: Aim: Despite improvement in preterm survival, neurological morbidity remains high. 3D fractional moving blood volume (3D‐FMBV) quantifies neonatal cerebral perfusion by calculating a standardised measure of the amount of moving blood in a region of interest and correlates with tissue perfusion in animal studies. However, its feasibility and reproducibility are yet to be assessed in newborn infants. Methods: Fractional moving blood volume analysis was performed on three‐dimensional power Doppler ultrasound (PD‐US) volumes from a cohort of preterm infants recruited in 2015 from the Royal Hospital for Women Neonatal Intensive Care Unit. The volumes were acquired by two sonographers and analysed by two different observers. The 3D‐FMBV algorithm was applied to calculate an estimate for perfusion. Reproducibility and agreement were assessed using intra‐class correlation coefficients (ICC) and Bland‐Altman plots. Results: All 3D PD‐US volumes were analysed successfully. Intra‐observer reliability was excellent with an ICC of 0.907 (95% CI 0.751–0.968) and 0.906 (95% CI 0.741–0.967) for two independent observers respectively. The inter‐observer reliability of the entire technique was good with an ICC of 0.752 (CI: 0.404–0.909). Conclusion: We have successfully shown the feasibility and reliability of applying the 3D‐FMBV technique to the neonatal brain in a healthy preterm population.